Blended families and their constitutional protection new considerations regarding the Medina Menendez case - Meza Figueroa, Mosi Marcela (2019)
The fulfillment of the constitutional duty of the State to protect the family requires an understanding of its dynamic nature. The purpose of this article is to analyze the legal implications of the new family structures, in particular those known as blended families, from their recognition in constitutional jurisprudence, in order to achieve their optimal protection.